2022
DOI: 10.3390/jpm12081194
|View full text |Cite
|
Sign up to set email alerts
|

A Personal Prospective on Testosterone Therapy in Women—What We Know in 2022

Abstract: Hormone replacement therapy continues to be a controversial topic in medicine, with certain narratives regarding safety concerns that are not scientifically established in peer-reviewed literature. These negative narratives, specifically undermining the use of testosterone in women, have caused women to remain without any Food and Drug Administration (FDA)-approved testosterone therapies, while more than 30 FDA-approved testosterone therapies are available for men in the United States. This has resulted in mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Ademais, o início do climatério pode cursar juntamente com a disfunção de Desejo Sexual Hipoativo (DSH), que afeta por volta de uma a cada dez mulheres na atualidade, caracterizado também pelo sofrimento referente à perda ou redução do interesse sexual feminino. Em contrapartida, pesquisas retratam melhora da sintomatologia a partir da suplementação hormonal, a qual mostrou que a administração subcutânea é ainda mais eficaz na manutenção de perfis lipídicos dentro da normalidade (Donovitz, 2022).…”
Section: Resultados E Discussõesunclassified
“…Ademais, o início do climatério pode cursar juntamente com a disfunção de Desejo Sexual Hipoativo (DSH), que afeta por volta de uma a cada dez mulheres na atualidade, caracterizado também pelo sofrimento referente à perda ou redução do interesse sexual feminino. Em contrapartida, pesquisas retratam melhora da sintomatologia a partir da suplementação hormonal, a qual mostrou que a administração subcutânea é ainda mais eficaz na manutenção de perfis lipídicos dentro da normalidade (Donovitz, 2022).…”
Section: Resultados E Discussõesunclassified
“…Studies have shown that free testosterone levels in women are closely associated with ovarian function and metabolic disorders in women [51] . The current clinical use of testosterone in the treatment of invasive breast cancer in women has also achieved good e cacy [52] . Testosterone levels in women have also shown signi cant correlations with depression, cognitive function, and cardiovascular system diseases in women [53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…Hormone pellet implants function by forming a capillary network around them, allowing hormone absorption to be dependent on cardiac output (36). There are only two studies, reviewed by Parish et al in 2021, that investigate the use of testosterone implants in treating sexual dysfunction (9).…”
Section: Testosterone Therapy: Evidence For Its Role In Enhancing Sex...mentioning
confidence: 99%
“…Given the absence of standardized methods for measuring testosterone levels in the bloodstream, involves adopting an individualized dosing algorithm. This strategy focuses on tailoring the dosage to reduce clinical symptoms specific to the patient while ensuring that serum levels are maintained at a threshold low enough to minimize any potential androgenic side effects (36).…”
Section: Testosterone Therapy In Hsdd: Safety and Managementmentioning
confidence: 99%
See 1 more Smart Citation